Scanning Electron Microscopy Reveals the Antennal Micromorphology of Lamprodila (Palmar) festiva (Coleoptera: Buprestidae), an Invasive Pest of Ornamental Cupressaceae in Western Palaearctic - Michel J. Faucheux; Tamás Németh; Johana Hoffmannova; Robin Kundrata (Biology, 2020)
The Cypress jewel beetle, Lamprodila (Palmar) festiva festiva (Linnaeus, 1767), is a serious invasive pest of ornamental Cupressaceae, which has recently expanded its range from the Mediterranean region northwards to central and eastern Europe, and to the Russian Black Sea coast. In this study, we conducted a scanning electron microscopy study of the micromorphology of the male and female antennae of L. festiva to examine the morphology, numbers, distribution, and possible functions of antennal sensilla. Most sensilla are located in the sensory fields within the apical depressions on antennomeres IV–XI. We identified four main types of antennal sensilla in L. festiva: sensilla chaetica (seven subtypes, of which two occur only in females), sensilla basiconica (five subtypes), multiporous grooved pegs (two subtypes), and Böhm sensilla. Females have relatively more sensilla chaetica and multiporous grooved pegs, whereas males have more sensilla basiconica. We discuss possible functions of all examined sensilla and compare them with those in other Buprestidae or other insects. Our study should serve as background information for advanced electrophysiological and behavioral experiments to better understand the functions of different sensilla and mechanisms related to semiochemically based pest control strategies.